EVALUASI SISTEM PENGENDALIAN INTERN DALAM PEMBERIAN KREDIT USAHA RAKYAT (KUR) PADA BANK SULTRA - Dian Astuti; Abdul Razak; Rachmawati (STIE ENAM ENAM KENDARI, 2022)
This study aims to determine the internal control system for the provision of People's Business Credit (KUR) at Bank Sultra, as well as to identify the inhibiting and supporting factors in the provision of People's Business Credit (KUR) at Bank Sultra. This study employed descriptive qualitative research. Data collection techniques included interviews and documentation. The results indicate that the internal control system for the provision of People's Business Credit at Bank Sultra can be considered effective in carrying out the company's operations, particularly in the provision of People's Business Credit (KUR), as well as the supporting and inhibiting factors in the provision of People's Business Credit (KUR).